2013
DOI: 10.1673/031.013.2201
|View full text |Cite
|
Sign up to set email alerts
|

The Sublethal Effects of the Entomopathic FungusLeptolegnia chapmaniion Some Biological Parameters of the Dengue VectorAedes aegypti

Abstract: The mosquito Aedes aegypti (L.) (Diptera: Culicidae) is the primary vector of dengue in the Americas. The use of chemical insecticides is recommended during outbreaks of dengue in order to reduce the number of adult mosquitoes; however, because Ae. aegypti is highly synanthropic, the use of insecticides in densely populated areas is a dangerous practice. Leptolegnia chapmanii Seymour (Straminipila: Peronosporomycetes) is an entomopathogenic microorganism that has demonstrated marked pathogenicity toward the la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
13
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 20 publications
3
13
0
Order By: Relevance
“… 40 Moreover, decreased survival and fecundity with increasing doses of entomopathogenic fungi have been reported. 41 , 42 The results are similar in the current research; housefly longevity and fecundity were both reduced after exposure to a sublethal dose (1 × 10 6 spores/mL) of different entomopathogenic fungi compared to controls. The differences in housefly longevity and fecundity might be due to the virulence potential of the fungus and/or the susceptibility of houseflies.…”
Section: Discussionsupporting
confidence: 86%
“… 40 Moreover, decreased survival and fecundity with increasing doses of entomopathogenic fungi have been reported. 41 , 42 The results are similar in the current research; housefly longevity and fecundity were both reduced after exposure to a sublethal dose (1 × 10 6 spores/mL) of different entomopathogenic fungi compared to controls. The differences in housefly longevity and fecundity might be due to the virulence potential of the fungus and/or the susceptibility of houseflies.…”
Section: Discussionsupporting
confidence: 86%
“…demonstrated that both B. thuringiensis ‐ and B. bassiana ‐based formulations were slightly to moderately toxic to honey bees. Sublethal effects on female Aedes aegypti fertility and wing length were shown after exposure to the entomopathogenic fungus Leptolegnia chapmanii, similar effects may be expected with B. bassiana infection.…”
Section: Discussionsupporting
confidence: 55%
“…aegypti ) and tested groups (treated and control) were randomly aspirated and maintained in separate cages. Then, all the individuals were anesthetized with 60% alcohol and the right wing of each individual was detached from the thorax and the length from the axial vein to the outmost extreme of the R1 vein 50 was measured using a stereomicroscope (100×) ( Fig. 3 ).…”
Section: Methodsmentioning
confidence: 99%